The Role of Physical Education in Improving Students Mental and Emotional Health - Muhammad Rajab; Wahyu Kurniadi (Siber Nusantara Review, 2024)
Physical education plays a crucial role in shaping not only students physical fitness but also their mental and emotional well-being. The pressures of academic demands, social challenges, and digital distractions have made students increasingly vulnerable to stress and anxiety. Through structured physical activities, teamwork, and positive social interactions, physical education contributes to the development of emotional stability, stress management, and self-confidence among students. This study aims to analyze the role of physical education in improving students mental and emotional health through participation in sports and physical activities. Using a qualitative descriptive approach, this paper discusses relevant psychological and educational theories to explain the positive effects of physical activity on emotional regulation and mental resilience. The findings highlight that consistent participation in physical education fosters a balanced lifestyle, enhances mood, and supports students overall well-being. Thus, physical education should be viewed as an essential component of a holistic education system that nurtures both the body and mind.